Contribution of area-based fisheries management measures to fisheries sustainability and marine conservation: a global scoping review - Dimitra Petza; Panagiotis Anastopoulos; Stefanos Kalogirou; Marta Coll; Serge Garcia; Michel Kaiser; Nikoletta Koukourouvli; Irene Lourdi; Jake Rice; Marija Sciberras; Stelios Katsanevakis (Reviews in Fish Biology and Fisheries, 2023)
Area-based fisheries management measures (ABFMs) are commonly related to the sustainable use of resources but are increasingly considered broader conservation measures. This Scoping Review (ScR) identified and mapped the evidence base regarding the contribution of ABFMs to fisheries sustainability and marine conservation. The ScR was conducted following the JBI methodology and the PRISMA statement. A total of 2,391 documents were identified, and following a two-stage screening process, 151 documents were eventually included in the ScR for full review and data extraction. Most of the documents were published during the last 12 years. Studies had a wide geographical distribution (mainly located in Europe and North America), were primarily conducted at the subnational level, concerned fishing restrictions of towed gears, and assessed ABFMs from a single stock’s perspective. ABFMs identified were of various types, and the use of terminology was not consistent in the literature. Multiple combinations of data collection (primarily experimental surveys/sampling and open data sources) and analysis methods (most commonly, fisheries and ecological analyses and modelling) were applied (often in combination), using a variety of different metrics. Various knowledge gaps emerged, mainly related to the study of ABFMs networks and the application of an interdisciplinary and ecosystem-based approach for assessing ABFMs. The social, economic, and environmental impact of ABFMs was positive in most cases (56%) and in less cases negative (22%) or mixed (14%). This ScR is a valuable source of information for the contribution of ABFMs to rebuilding marine ecosystems and attaining CBD conservation targets through the lens of the OECM concept. Graphical abstract

OECMs in marine capture fisheries: Key implementation issues of governance, management, and biodiversity - Serge Michel Garcia; Jake Rice; Amber Himes-Cornell; Kim Jerome Friedman; Anthony Charles; Daniela Diz; Joseph Appiott; Michel J. Kaiser (Frontiers in Marine Science, 2022)
The ‘Other Effective Area-based Conservation Measure’ (OECM) concept was first introduced in 2010, by the Conference of the Parties of the Convention on Biological Diversity (CBD COP) in the CBD Strategic Plan for Biodiversity conservation 2011–2020. The concept acknowledged that a range of spatial measures other than protected areas were appropriate for reaching Aichi Target 11 spatial conservation coverage. The OECM definition was adopted in 2018 in CBD COP Decision 14/8, which calls on States to mainstream OECMs into economic sectors, to recognize the current biodiversity conservation benefits and co-benefits from their area-based management measures and enhance them as much as possible. In the marine capture fisheries sector, the identification of OECMs is a work in progress and the issues addressed in this paper are key implementation issues that States and fisheries authorities are or will be encountering regarding their governance, management, and biodiversity outcomes. The purpose of the paper is to draw attention to some key OECM implementation issues arising in marine capture fisheries and to suggest possible approaches to address them. The governance issues addressed relate to enabling frameworks, industrial fisheries, legitimate authorities, long-term commitments, cross-sectoral coordination and planning, and contribution to the Post-2020 Global Biodiversity Framework of the CBD. The management issues considered relate to effectiveness in achieving expected outcomes, costs and benefits of OECMs, spatial relations between OECMs and fisheries, and the role of OECMs in the Ecosystem Approach to Fisheries (EAF). Regarding the significant positive biodiversity outcomes expected from OECMs, issues relate to the type of outcomes expected, their current or intended nature, the level of evidence required, and their relationship to area-based conservation standards.

Reaching Global Marine Biodiversity Conservation Goals With Area-Based Fisheries Management: A Typology-Based Evaluation - Amber Himes-Cornell; Juan Francisco Lechuga Sánchez; Caroline Potter; Clayton McKean; Jake Rice; Kim J. Friedman; Serge M. Garcia; Dave L. Fluharty (Frontiers in Marine Science, 2022)
In 2010, the Parties to the Convention on Biological Diversity (CBD) adopted the Aichi Biodiversity Target 11, calling for conserving 10% of the ocean through marine protected areas (MPAs) and “ other effective area-based conservation measures ” (OECMs), explicitly recognizing that other types of spatial conservation measures beyond areas designated as MPAs may also achieve biodiversity gains. Eight years later, CBD Parties adopted a definition and criteria for OECMs, and by early 2022, only a few OECMs had been reported. The OECM definition clearly requires that the measures be area-based and likely to contribute to conservation. However, conservation need not be their primary objective. Guidance on the extent and limits of what these “area measures” might include is needed. Clarity would assist countries in delivering on the CBD’s Post-2020 Global Biodiversity Framework, with decadal goals incorporating an area-based conservation target, in which OECMs will play a crucial role. To achieve greater recognition of OECMs, countries require sector-specific guidance to guide recognition, listing, and ongoing implementation of OECMs. Here, we evaluate how well area-based fisheries management measures meet the OECM criteria as well as sustainable use principles, broader ecosystem management objectives, and more general biodiversity conservation goals. We systematically review case studies across a broad range of spatial management approaches to provide evidence of correspondence with the OECM criteria, arguing that many with primary objectives related to fisheries sustainability provide co-benefits for biodiversity, and hence biodiversity conservation and sustainable development. This review highlights how fisheries measures can help achieve a number of Sustainable Development Goals alongside the global targets for biodiversity of CBD.

A Contrast of Criteria for Special Places Important for Biodiversity Outcomes - Jake Rice; Kim Friedman; Serge Garcia; Hugh Govan; Amber Himes-Cornell (Frontiers in Marine Science, 2022)
This paper contrasts seven spatial biodiversity conservation area designations by six different bodies: Other Effective Area-Based Conservation Measures (OECMs), and the Ecologically and Biologically Significant Areas (EBSAs) of the Convention on Biological Diversity (CBD); the Vulnerable Marine Ecosystems (VMEs) of the Food And Agriculture Organization (FAO); the Key Biodiversity Areas (KBAs) under criteria developed by the IUCN; the Areas of Particular Environmental Interest (APEIs) of the International Seabed Authority (ISA); the Particularly Sensitive Sea Areas (PSSAs) of the International Maritime Organization (IMO); and the Locally Managed Marine Areas (LMMAs) used by small island States in the Pacific Ocean; on five themes: biological and ecological features, functions served by areas receiving these labels, governance, threats and pressures, and other considerations. The seven different labels for such areas were generally similar in the biologically and ecological criteria to be met, and the functions typically served by these areas. Differences among the labels increased when considering governance, threat and pressures, and other considerations. Implications of these similarities and differences for policy development and outcomes are discussed. Performance reviews of the various labels under these themes could provide insight into both the effectiveness of the provisions in the Agreements and Decisions and how evidence is acquired and used to inform their application, allowing improvements to each approach to learn from experiences with other labels.

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Balanced harvest: concept, policies, evidence, and management implications - Shijie Zhou; Jeppe Kolding; Serge M. Garcia; Michael J. Plank; Alida Bundy; Anthony Charles; Cecilie Hansen; Mikko Heino; Daniel Howell; Nis S. Jacobsen; David G. Reid; Jake C. Rice; et al. (Reviews in Fish Biology and Fisheries, 2019)

A framework for evaluating management plans comprehensively - Verena M Trenkel; Marie‐Joëlle Rochet; Jake C Rice (Fish and Fisheries, 2015)
We present a framework for evaluating fisheries management plans comprehensively, both rebuilding plans and others. The framework includes a first rapid appraisal of the likelihood that the plan will result in management meeting its objectives, and guides subsequent quantitative analyses of potential weaknesses in the proposed plan. The framework includes four steps: (i) evaluating if a set of management objectives, if achieved, would result in a sustainable fishery, (ii) using qualitative analysis of a bio‐economic model to evaluate whether the set of stock management tactics might be capable of achieving the specified fisheries objectives, (iii) using empirical criteria derived from the literature to evaluate if other management measures in the plan related to the ecological, social or economic context of the fishery actually contribute to sustainability, and (iv) carrying out quantitative simulations to compare alternative implementation options. Generally, several management measures have to be combined to increase stock size without sacrificing the economic benefits to the fishers remaining in the fishery. We demonstrate application of the framework for evaluating the stock rebuilding plan for plaice ( Pleuronectes platessa ) and sole ( Solea solea ) in the North Sea and, the management measures currently in place for the roundnose grenadier ( Coryphaenoides rupestris ) stock exploited to the west of the British Isles.

Managing fisheries well: delivering the promises of an ecosystem approach - Jake Rice (Fish and Fisheries, 2011)
The four general components of an ecosystem approach to fisheries (EAF) are reviewed. In taking account of environment forcing in stock dynamics, arguments are presented that effects of environmental forcing on growth, maturation and natural mortality are often more important to management than effects on recruitment. In holding fisheries accountable for the ecosystem effects of fishing, it is argued that direct effects of fishing are generally known and can be managed. However, interactions among fisheries and between fisheries and other sectors pose difficult challenges to equitable decisions in managing these impacts, and many traditional incentives function differently in EAF than in target‐stock management. Achieving inclusiveness in decision‐making and stewardship is also made more complex in EAF, because of the much larger number of interests with a legitimate role in decision‐making. As a result, integrated management (IM) becomes a necessary component of EAF, although EAF and IM are not interchangeable concepts. The treatment of all four components of an EAF considers the need for a balanced and stable outcome on all three dimensions of sustainability – ecological, economic and social. It also highlights that different participant groups in governance display different risk tolerances for misses (not taking conservation action when needed) and false alarms (restraining access to social or economic benefits when little ecological benefit results). These differences in tolerances for different kinds of management errors often complicate decision‐making an EAF setting and raise transaction costs greatly.

Towards an ecosystem approach to fisheries in Europe: a perspective on existing progress and future directions - Simon Jennings; Jake Rice (Fish and Fisheries, 2011)
European countries are committed to adopting an ecosystem approach. These commitments are expected to influence the forthcoming reform of the Common Fisheries Policy (CFP) and thus progress towards implementing an ecosystem approach to fisheries (EAF). We suggest that the major impediments to adopting an EAF in the current CFP are the low specificity and incompatibility of environmental, social and economic objectives, no agreed guidance on the priority to be given to objectives when trade‐offs have to be made, a decision‐making system that is strongly influenced by short‐term national interests, and low societal and political will to pay the high short‐term costs of making the transition to sustainability. Notwithstanding, a high‐level policy framework to support the ecosystem approach and EAF, along with many of the tools needed to support an operational system, is now emerging. The rate of progress towards an operational EAF following CFP reform will be influenced by the requirement for a reformed management system to help achieve Good Environmental Status for ecosystem components and attributes, in support of European policy for the marine environment (principally the Marine Strategy Framework Directive). However, the willingness and capacity of member states to meet high short‐term transition costs, the extent of their support for transferring tactical decision‐making to regional bodies and their views on acceptable transition rates are likely to have more influence on progress towards meeting the objectives of an EAF.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Size, growth, temperature and the natural mortality of marine fish - Henrik Gislason; Niels Daan; Jake C Rice; John G Pope (Fish and Fisheries, 2010)
The natural mortality of exploited fish populations is often assumed to be a species‐specific constant independent of body size. This assumption has important implications for size‐based fish population models and for predicting the outcome of size‐dependent fisheries management measures such as mesh‐size regulations. To test the assumption, we critically review the empirical estimates of the natural mortality, M (year −1 ), of marine and brackish water fish stocks and model them as a function of von Bertalanffy growth parameters, L (cm) and K (year −1 ), temperature (Kelvin) and length, L (cm). Using the Arrhenius equation to describe the relationship between M and temperature, we find M to be significantly related to length, L and K , but not to temperature ( R 2 = 0.62, P n = 168). Temperature and K are significantly correlated and when K is removed from the model the temperature term becomes significant, but the resulting model explains less of the total variance ( R 2 = 0.42, P n = 168). The relationships between M , L , L , K and temperature are shown to be in general accordance with previous theoretical and empirical investigations. We conclude that natural mortality is significantly related to length and growth characteristics and recommend to use the empirical formula: ln( M ) = 0.55 − 1.61ln( L ) + 1.44ln( L ) + ln( K ), for estimating the natural mortality of marine and brackish water fish.